Verification of the Qibla Direction of Jami' Nurul Huda Mosque, Cangakan Village, Kanor, Bojonegoro - Jannah, Elly Uzlifatul; Idris Rahmat; Isna Putri Sa’adah; Imroatul Mufidah (Universitas Islam Negeri Mataram, 2024)
Jami' Nurul Huda Mosque is one of the oldest mosques in Bojonegoro, with an age of approximately one and a half centuries. This mosque was founded by a Mataram Islamic warrior named Ki Ageng Wiroyudo in 1846 AD or 1262 Hijri. The purpose of this research is to determine the accuracy of the qibla direction of Jami' Nurul Huda Mosque in Cangakan, Kanor, Bojonegoro. This research is a field study with a descriptive qualitative approach. The primary data sources used are interviews with the mosque's management and observations. The results of this research conclude that the qibla direction of Jami' Nurul Huda Mosque in Cangakan, Kanor, Bojonegoro, when measured using the Mizwala Qibla Finder, shows an azimuth value of 302° compared to the qibla azimuth value of 294° 41’59”, resulting in a difference of 8°. When calculated using Google Earth, the mosque building shows an azimuth value of 303°30’36” and a qibla azimuth value of 294°10'48